2012
DOI: 10.3390/molecules171112910
|View full text |Cite
|
Sign up to set email alerts
|

Quantitative Studies on Structure-DPPH• Scavenging Activity Relationships of Food Phenolic Acids

Abstract: Phenolic acids are potent antioxidants, yet the quantitative structure-activity relationships of phenolic acids remain unclear. The purpose of this study was to establish 3D-QSAR models able to predict phenolic acids with high DPPH• scavenging activity and understand their structure-activity relationships. The model has been established by using a training set of compounds with cross-validated q2 = 0.638/0.855, non-cross-validated r2 = 0.984/0.986, standard error of estimate = 0.236/0.216, and F = 139.126/208.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
40
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 55 publications
(44 citation statements)
references
References 29 publications
4
40
0
Order By: Relevance
“…These two phenolic acids showed good antioxidant activities in DPPH assay (22.71 and 35.17 μM, respectively), but antioxidant activity of their corresponding triazoles was significantly higher ( p < 0.05). Literature data confirm high radical scavenging activities of 1 f and 1 h , while phenolic acids with one hydroxyl group, such as 1 a , 1 b and 1 c show negligible antioxidant capacities . Our results showed that phenolic acids with two hydroxyl groups, such as 1 g and 1 i are better antioxidants than monohydroxy acids, but their activity is also low.…”
Section: Resultssupporting
confidence: 68%
“…These two phenolic acids showed good antioxidant activities in DPPH assay (22.71 and 35.17 μM, respectively), but antioxidant activity of their corresponding triazoles was significantly higher ( p < 0.05). Literature data confirm high radical scavenging activities of 1 f and 1 h , while phenolic acids with one hydroxyl group, such as 1 a , 1 b and 1 c show negligible antioxidant capacities . Our results showed that phenolic acids with two hydroxyl groups, such as 1 g and 1 i are better antioxidants than monohydroxy acids, but their activity is also low.…”
Section: Resultssupporting
confidence: 68%
“…The presence of electron donating or high electron density hydroxyl group at meta and para positions of gallic acid attributes to the high scavenging ability of gallic acid (Jing et al 2012 Fig. 1 Structure of the phenolic compounds assayed for free radical scavenging exhibited higher scavenging activity (38.9 %) than veratryl alcohol (0.38 %) due to para-hydroxy substitution.…”
Section: Resultsmentioning
confidence: 99%
“…As previously reported, hydroxylation in adjacent carbons (o-diphenyl structure) enhances antioxidant activity. 54 Jing and co-workers 55 also outlined that the presence of: (i) bulky and/or electrondonating substituents on the aromatic ring, (ii) electron-donating groups at the meta position and/or hydrophobic groups at the meta-ortho position, and (iii) hydrogen bond donor/electrondonating groups at the ortho position strengthen the antioxidant activity of phenolic acids. Hydroxylation and/or methoxylation on the C ring affects the antioxidant activity of anthocyanins.…”
Section: Relationship Between Phenolics Structure and Antioxidant Capmentioning
confidence: 99%